TIRTA Coaching-Based for Academic Supervision to Improve Teacher Professionalism - Mawarni, Mawarni; N, Najmuddin; Ilyas, Mukhlisuddin (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study explores the implementation of coaching-based academic supervision using the TIRTA framework to enhance teacher professionalism in two “Sekolah Penggerak” junior high schools, SMPN 1 Muara Tiga and SMPS Sukma Bangsa, in Pidie Regency, Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews, classroom observations, documentation, and teacher performance analysis to ensure comprehensive and reliable findings. The TIRTA framework, integrating the GROW Model with stages of Goal, Reality Identification, Reflection, Challenges, and Action, fosters a dialogic, reflective, and empowering supervision process, shifting principals’ roles from authoritative evaluators to facilitators of professional learning, as supported by Cognitive Apprenticeship Theory by Collins, Brown, & Newman. The results shows indication that TIRTA-based coaching enhances teachers’ reflective practices, intrinsic motivation, and pedagogical skills, with 72% of teachers reporting significant improvements in their teaching abilities. The approach promotes a collaborative and independent school culture, aligning with Transformational Leadership Theory by Burns, and Kolb’s Experiential Learning Theory. Despite challenges in time management, the TIRTA model proves effective in fostering continuous professional development and improving instructional quality, contributing to long-term educational advancements.